Character Education Management Through Religious Habituation in Junior High School - Faiq Akmaluddin Hafidzh; R. Madhakomala (Interdisciplinary Journal of Advanced Research and Innovation, 2024)
Character is a form of behavior of a person that is related to actions, words, feelings, attitudes, thoughts, environment, social, self, and relationship to God based on current regulations. Religious character is the behavior shown to a person to carry out what is commanded in Islam and stay away from all forms of His prohibitions. In another context, Indonesia is a Pancasila country, where the first principle explains "Belief in One Almighty God". Education at school can be used as a madrasa for children to deepen their religious knowledge, so that religious character can be formed from these activities. The aim is to analyze the management of character education through religious habituation in junior high schools. The research method uses qualitative research with a literature review approach. The results obtained by character education are one of the forms of education that must be implemented at the secondary education level. Religious values are one of the values that students can familiarize themselves with as a form of character education management. In implementing religious habits, teachers have various roles, especially in character education managementReligious habits in implementing character education can be influenced by several factors, including infrastructure, school environment, student interests, and student background.